Implementing Circular Supply Chains in Indonesia: The Case of Rekosistem and Implications for FMCG Companies - Jejen Zauharudin; Hervina Dwi Yuniar; Luthfi Farizky Supriyono; Marsya Heilma Aulia; Vita Sarasi; Budi Harsanto (Lembaga Pengembangan Kinerja Dosen, 2026)
The transition from linear to circular supply chains is increasingly recognized as a strategic necessity rather than merely a corporate social responsibility initiative (MahmoumGonbadi et al., 2021; Mishra et al., 2023; Montag, 2023). This paper examines the implementation of sustainable and circular supply chains in Indonesia by using Rekosistem as the primary case study and Danone and Nestlé as examples of corporate partners within the circular ecosystem. Conceptually, circular supply chains build upon the principles of closed-loop supply chains, reverse logistics, and the circular economy, emphasizing material recovery, value recapture, and the integration of forward and reverse flows to generate economic, social, and environmental value simultaneously (MahmoumGonbadi et al., 2021; Mishra et al., 2023). In Indonesia, the need for circular supply chains is driven by persistent plastic waste challenges, the critical role of the informal sector, limited recycling infrastructure, and growing corporate sustainability commitments (Iacovidou et al., 2025; Pambudi et al., 2025). This paper argues that successful circular supply chain implementation in emerging markets depends on three interrelated factors: data visibility, effective coordination between formal and informal actors, and corporate demand driven by ESG objectives and Scope 3 decarbonization targets (Danone Group in Indonesia, 2023; Nestlé, 2025; Simonetto et al., 2022).